Inaccuracy of the State Attorney in Drafting a Lawsuit that Causes a Non-Executable Judgement: Case Study in Civil Case No. 06/Pdt. G/2015/PN.Bbs - Puspita, Natalia Diah Ayu; Christy, Maria Acynta (The Digest: Journal of Jurisprudence and Legisprudence, 2024)
Verdict Number: 06/Pdt.G/2015/PN.G/2015/PN.Bbs cannot be executed, even though it has become inkracht (final and binding). This situation contradicts the indicators of law enforcement assessment, which state that civil courts should not face unreasonable delays, must enforce decisions effectively, and must uphold the objectives of achieving justice, expediency, and legal certainty. This research examines the plaintiff's errors in preparing the lawsuit, which led to the non-executable verdict, and explores how to properly draft a lawsuit to ensure its execution. This study is normative legal research, where the research materials are analyzed qualitatively and presented descriptively. The findings of this research reveal that several mistakes made by the plaintiff contributed to the verdict’s non-execution. These errors include the plaintiff’s failure to include non-punitive claims and to attach a request in the lawsuit. The plaintiff also did not provide the title deed for the disputed land, and the positum and petitum were drafted asynchronously, with the claim for compensation mixed with the request for dowry. It is essential for the plaintiff to be meticulous when drafting the petitum, as any errors in this stage can impact the judge’s decision. The lawsuit must be prepared thoroughly and specifically, stating the legal grounds and structuring the petitum in accordance with these grounds and the factual circumstances. Additionally, the plaintiff should avoid combining compensation claims with requests for dwangsom (penal sanctions) in the same petitum.